Cover Picture: Ambient Synthesis of One‐/Two‐Dimensional CuAgSe Ternary Nanotubes as Counter Electrodes of Quantum‐Dot‐Sensitized Solar Cells (ChemPlusChem 4/2016). Issue 4 (12th February 2016) - Chen, Xin Qi; Bai, Yang; Li, Zhen; Wang, Lian Zhou; Dou, Shi Xue
Abstract : The cover picture shows ternary copper silver selenide nanotubes prepared from copper selenide nanotubes through a simple cation‐exchange reaction. The new material was explored as high‐performance counter electrodes in quantum‐dot‐sensitized solar cells and achieved high conversion efficiency ( η =5.61 %). Details are given in the Full Paper by Zhen Li et al. on page 414 in Issue 4, 2016 (DOI: 10.1002/cplu.201500466 ).